Unidunitê: identidades, juveni- etnocídio e a Pastoral da Juventude na defesa dos Direitos Humanos dos jovens no Piauí - Andrade, Carlos Alberto Amorim de Sousa (2023)
We can understand youth as just an age group, a transition from infant to adult, or a vital state of mind. Gathering these understandings, the research proposed to understand the phenomena of youth and to fill a historical gap about the action of the Pastoral da Juventude in defense of the human rights of young people in Piauí, based on the pedagogies and theologies that are the foundation of this pastoral, and also to analyze the phenomenon of violence, which in recent decades has been challenging contemporaneity, and which profoundly reaches the population comprised in the age group of 15 to 29 years, where the largest cases of "juvenile ethnicity" are concentrated in Brazil. With the growth of violence among young people, mainly due to exogenous causes, which is directly linked to various social indicators such as social inequality, high rates of poverty, drug trafficking and, in contrast, a deficit of public policies aimed at this age group, the fruit of the culture of violence and necropolitics, the promoted discussion concludes that this violence has defined sex, color and social class - young people, men, blacks and poor. In the face of this devastating scenario, which presents Brazil in seventh place in the world ranking as the country that most kills its youth, in the year 2008, at the 15th National Assembly of Youth Pastoral Care in Brazil, the National Campaign Against Violence and the Extermination of Young People was proposed, in order to foster political formation and grassroots work, mass actions and dissemination, as well as media monitoring to denounce the violation of human rights, from the pastoral project "Youth wants to Live." In this way, the catalytic nature of changes in social movements and the active participation of the Pastoral da Juventude in defense of the lives of the young Piauí women was once again highlighted. Thus, the general objective of the research was to analyze the violation of the human rights of poor and black youth in the State of Piauí considering the phenomena of violence and criminalization and the action of the Pastoral da Juventude in defense of the young (1970/2019); specific objectives: to relate the historical milestones of youth ministry with the dimensions/generations of human rights; study the phenomenon of violence and criminalization of the young, poor and black population in Brazil and Piauí; understand the role of the State in combating violence against youth; to reflect the actions of the Pastoral da Juventude in the realization of the rights of the youths from the perception of the youths of this organization. From this perspective, the methodology used was the quantitative and qualitative categories, listening to 8 groups of young people from the Pastoral de Juventude - PJ. In this listening, through the instruments of the focus group, the inductive method was used. Data from the Map of Violence and the Public Security Secretariat of the State of Piauí were also compared, in a time frame of a decade, from the years 2009 to 2019. Oral history permeated part of the methodology of the dissertation and integrative literature review, primary and secondary sources, with emphasis on the years 2009 to 2019 (before the Covid 19 pandemic), a period of effervescence of discussions and the protagonism of youth in relation to public policies in the Brazilian state.